Cognitive Pragmatic Rehabilitation Program in Schizophrenia: A Single Case fMRI Study - Ilaria Gabbatore; Francesca M. Bosco; Elisabetta Geda; Luigi Gastaldo; Sergio Duca; Tommaso Costa; Bruno G. Bara; Katiuscia Sacco (Neural Plasticity, 2017)
Introduction. The present study was intended to evaluate the effects of a rehabilitative training, the Cognitive Pragmatic Treatment (CPT), aimed at improving communicative-pragmatic abilities and the related cognitive components, on the cerebral modifications of a single case patient diagnosed with schizophrenia. Methods. The patient underwent two functional magnetic resonance imaging (fMRI) sessions, before and after the treatment. In order to assess brain changes, we calculated the Amplitude of Low Frequency Fluctuation (ALFF) index of the resting-state fMRI signal, which is interpreted as reflecting the intensity of the spontaneous regional activity of the brain. Behavioural measures of the patient’s communicative performance were also gathered before and after training and at follow-up. Results. The patient improved his communicative performance in almost all tests. Posttraining stronger ALFF signal emerged in the superior, inferior, and medial frontal gyri, as well as the superior temporal gyri. Conclusions. Even if based on a single case study, these preliminary results show functional changes at the cerebral level that seem to support the patient’s behavioural improvements.